Effect of Progestin based Estrus Synchronization Protocol on Estrus Parameters, Hormonal Profile and Vaginal Cytology in Surti Goats - Patel, Sanjay; Chaudhary, Sandhya; Puri, Gopal; Singh, Virendra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This investigation was conducted to study the effect of progestin and prostaglandin-based estrous synchronization protocol on estrus parameters, hormonal profile and vaginal cytology in Surti goats. Ten non-pregnant Surti goats were selected and subjected to estrus synchronization with intra-vaginal progesterone sponges (60 mg Medroxyprogesterone acetate, MAP) for 11 days followed by PGF2α injection (125 μgCloprostenol). Whole blood was collected on day 0 (before treatment), day 5, 11 (after treatment), at proestrus, estrus and diestrus for analyzing progesterone as well as estrogen hormone concentration. The vaginal exfoliative cytology was studied at proestrus, estrus and diestrus. Estrus parameters such as induction rate was 100%, time of onset of estrus from PG injection was 29.70 ± 1.06 h and duration was 30.74 ± 0.19 h. Significantly higher population of parabasal cells and superficial cells were observed during proestrus, intermediate cells in diestrus and cornified cells during estrus. At estrus, level of progesterone was lowest and estrogen was highest. Combination of progestin and prostaglandin-based protocol is successful in synchronization of estrous cycle with 100% estrus induction rate in Surti goats. Further in addition to other signs, vaginal exfoliative cytology can also be used for determining different phases of estrous cycle.
Keywords: Estrus synchronization; Estrus parameters; Hormones; Surti goat; Vaginal cytology